(untitled) (Al-Farooq Journal of Sciences, 2025)
This study aimed to examine the role of electronic accounting disclosure in improving the quality of accounting information in commercial banks operating in Az awiya City. The study adopted the descriptive-analytical approach and used a questionnaire as the primary tool for data collection from employees working in the financial and accounting departments, internal audit departments, and information technology departments in the banks under study. The findings revealed that the level of electronic accounting disclosure in the surv